A study of stratospheric GW fluctuations and sporadic e at midlatitudes with focus on possible orographic effect of Andes - Hocke, K. (2002)
Longitudinal dependences of stratospheric gravity wave (GW) fluctuations and lower ionospheric irregularities (sporadic E) at midlatitudes are studied by means of radio occultation data of the Global Positioning System/Meteorology Experiment (GPS/MET) satellite mission. The zonal average of temperature variance of GW fluctuations with vertical scales less than 7 km at northern midlatitudes is observed to be similar to that at southern midlatitudes, but there is a significant interhemispheric difference in the longitudinal dependence of GW fluctuations. The GPS/MET data at northern midlatitudes show a rapid change of the gravity wave distribution from 25 to 35 km height, resulting in a broad maximum of temperature variance located over the Atlantic and Eurasia. We only find in the wave distribution at h = 25 km some weak traces of possible orographic effects. On the other hand, the distribution of GW fluctuations at southern midlatitudes has a strong and sharp maximum over Andes, which is obviously due to orographic wave generation by the interaction of surface wind with the Andean mountain ridge. This observation of the new GPS radio occultation technique is in agreement with previous measurements of spaceborne microwave and infrared limb sounders. The amplitude of the average wave field increases with height over Andes, while the amplitude maximum moves westward, against the prevailing wind. The temperature fluctuations have an apparent, dominant vertical wavelength of around 6 km. In situ measurements by a balloon-borne rawinsonde at Ushuaia, Argentina (54.7°S, 68.1°W) are compared to a simultaneous GPS/MET temperature profile. The balloon observations of temperature and horizontal wind are interpreted by a large amplitude mountain wave propagating to the upper stratosphere. Wave characteristics and atmospheric background conditions are investigated in detail for this mountain wave observation. Finally, the GPS/MET experiment indicates enhanced sporadic E in the lower ionosphere over Southern Andes. We assume that these plasma irregularities are generated by enhanced, upward wave flux due to the possible orographic effect of Andes. Copyright 2002 by the American Geophysical Union.